Genetic, structural and clinical analysis of spastic paraplegia 4. (May 2022) - Varghaei, Parizad; Estiar, Mehrdad A.; Ashtiani, Setareh; Veyron, Simon; Mufti, Kheireddin; Leveille, Etienne; Yu, Eric; Spiegelman, Dan; Rioux, Marie-France; Yoon, Grace; Tarnopolsky, Mark; Boycott, Kym M.; et al.
Abstract: Introduction: Spastic paraplegia type 4 (SPG4), resulting from heterozygous mutations in the SPAST gene, is the most common form among the heterogeneous group of hereditary spastic paraplegias (HSPs). We aimed to study genetic and clinical characteristics of SPG4 across Canada. Methods: The SPAST gene was analyzed in a total of 696 HSP patients from 431 families by either HSP-gene panel sequencing or whole exome sequencing (WES). We used Multiplex ligation-dependent probe amplification to analyze copy number variations (CNVs), and performed in silico structural analysis of selected mutations. Clinical characteristics of patients were assessed, and long-term follow-up was done to study genotype-phenotype correlations. Results: We identified 157 SPG4 patients from 65 families who carried 41 different SPAST mutations, six of which are novel and six are CNVs. We report novel aspects of mutations occurring in Arg499, a case with homozygous mutation, a family with probable compound heterozygous mutations, three patients with de novo mutations, three cases with pathogenic synonymous mutation, co-occurrence of SPG4 and clinically isolated syndrome, and novel or rarely reported signs and symptoms seen in SPG4 patients. Conclusion: Our study demonstrates that SPG4 is a heterogeneous type of HSP, with diverse genetic features and clinical manifestations. In rare cases, biallelic inheritance, de novo mutation, pathogenic synonymous mutations and CNVs should be considered. Highlights: SPG4, as a heterogeneous type of HSP, has diverse genetic features and clinical manifestations. Six novel mutations and six CNVs were identified in our SPG4 cohort. Biallelic inheritance, de novo mutation and pathogenic synonymous mutations should be considered in some cases.